Experimental Study of Heat Transfer and Water Infiltration in Two-Layered Granular Packed Bed - Aksornkitti, Sauce; Rattanadecho, Phadungsak; Wessapan, Teerapot (Science & Technology Asia, 2022)
The characteristics of heat transfer and water infiltration by hot water into a twolayered two-dimensional granular packed bed have been investigated experimentally. This study aims to understand the influences of the layered configuration of the granular packed bed, supplied water temperature, and supplied water flux on the water infiltration and heat transport in the two-layered granular packed bed. The study illustrated the dynamics of heat transfer and water infiltration in various testing cases. The results showed that the layered configuration of the granular packed bed, supplied water temperature, and supplied water flux have significant effects on the water infiltration and heating pattern of the packed bed. In the case of smaller particles on top (FC-bed), the infiltration front tends to expand in the lateral direction faster than the downward direction. The higher supplied water temperature results in a deeper and wider infiltration. Furthermore, the heating zone is found to be moving a little slower than infiltration front propagation. The findings can be used as basic information for research on other purposes such as heat and water movement in the ground.